FRAGMENTS WITHIN FRAGMENTS: DISTANCING THROUGH THE PANGLINGAN PRINCIPLE IN PAINTING PRACTICE - Alamsyah, Tamara Maharani (ARTISTIC : International Journal of Creation and Innovation, 2025)
The creation of "Fragments within Fragments" originates from an analysis of the Mooi Indie phenomenon, which perceives the East Indies from a perspective of distance. This phenomenon illustrates how artworks from that era established a disparity between reality and its representation. In an era of easy and ubiquitous image production, manipulation that results in the alienation of experience frequently transpires unconsciously. Real objects and experiences are supplanted by images regarded as representations of reality. In this setting, art serves as a medium to depict images and their forms that are perceived illusorily. Through the panglingan (Sudjoko, 1992) of initially representative photographic images, blurring is created to distinguish the image from its representative elements. This process establishes a distance between subject and object, intensifying a sense of alienation between the image and its observer. This work fosters reflection on individuals' perceptions and experiences of objects in a digital era saturated with images that merely represent fragments of authentic experience by positioning the subject at a distance and inducing a sense of alienation through blurring.